Proceedings of the 15th Koli Calling Conference on Computing Education Research 2015
DOI: 10.1145/2828959.2828979
|View full text |Cite
|
Sign up to set email alerts
|

Exploring societal factors affecting the experience and engagement of first year female computer science undergraduates

Abstract: Despite computer science (CS) having many women associated with it historically, such as Ada Lovelace and Grace Hopper, the proportion of female students completing computing degrees is steadily declining, particularly in the USA, UK, and several other Western countries. Many initiatives have been attempted to address this gender imbalance, but the majority have proved to be ineffectual and difficult to sustain in the long term. One important step in the notorious shrinking participation pipeline for CS is the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In her study, "gendered socialization" (more support for boys) and "technology anxiety" were identified as key factors. In the UK, Sinclair and Kalvala [55] found that gender stereotypes (computer science for boys) and cultural expectations (parents' discouragement) were the significant factors that could influence the decisions of females not to study CS. Cohoon and Aspray [15] also argued that social and cultural factors affect gender participation in computing fields, not biological gender differences.…”
Section: Factors Influencing the Choice To Study Computer Sciencementioning
confidence: 99%
“…In her study, "gendered socialization" (more support for boys) and "technology anxiety" were identified as key factors. In the UK, Sinclair and Kalvala [55] found that gender stereotypes (computer science for boys) and cultural expectations (parents' discouragement) were the significant factors that could influence the decisions of females not to study CS. Cohoon and Aspray [15] also argued that social and cultural factors affect gender participation in computing fields, not biological gender differences.…”
Section: Factors Influencing the Choice To Study Computer Sciencementioning
confidence: 99%
“…There is a considerable disparity in the number of female students choosing to study Computer Science compared to male students at tertiary education level [3,4,14,31]. In the 1980's, Computer Science had one of the highest rates of gender balance in graduate programmes, but this has changed considerably in recent times [37].…”
Section: Motivationmentioning
confidence: 99%
“…Accompanying the website was a video that depicted female "scientists" conducting work in stiletto heels. This video was referred to as offensive and after criticism was removed [31]. Other initiatives such as Girls Who Code, SciGirls and GirlsInc have been created.…”
Section: Related Literaturementioning
confidence: 99%
“…1). Negative pressure from parents can have the greatest impact on girls not entering the field (Sinclair & Kalvala, 2015).…”
Section: Academic Environmentmentioning
confidence: 99%
“…al., 2014;Powell, 2008;Tillberg & Cohoon, 2005). Due to the limited sample sizes, it is difficult to confirm the validity of these findings (Scragg & Smith, 1998;Sinclair & Kalvala, 2015). DuBow et al (2017) conducted a larger qualitative study (64 participants) which examined women's persistence in computer science.…”
Section: Deficiencies In the Researchmentioning
confidence: 99%